2014
DOI: 10.1371/journal.pone.0106904
|View full text |Cite
|
Sign up to set email alerts
|

Beta-1 Adrenergic Agonist Treatment Mitigates Negative Changes in Cancellous Bone Microarchitecture and Inhibits Osteocyte Apoptosis during Disuse

Abstract: The sympathetic nervous system (SNS) plays an important role in mediating bone remodeling. However, the exact role that beta-1 adrenergic receptors (beta1AR) have in this process has not been elucidated. We have previously demonstrated the ability of dobutamine (DOB), primarily a beta1AR agonist, to inhibit reductions in cancellous bone formation and mitigate disuse-induced loss of bone mass. The purpose of this study was to characterize the independent and combined effects of DOB and hindlimb unloading (HU) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…The increase in alveolar bone tissue mass upon atenolol treatment in this study is consistent with the decreased risk of fracture upon atenolol treatment reported previously (Song et al, ; Toulis et al, ) but not with an atenolol‐induced decrease in bone mass owing to systemic stimuli that promotes IGF‐1 downregulation reported previously (Pierroz et al, ). This discrepancy may result from differences in mechanical stress, orthodontic force and the dynamic cyclic axial compression protocol.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The increase in alveolar bone tissue mass upon atenolol treatment in this study is consistent with the decreased risk of fracture upon atenolol treatment reported previously (Song et al, ; Toulis et al, ) but not with an atenolol‐induced decrease in bone mass owing to systemic stimuli that promotes IGF‐1 downregulation reported previously (Pierroz et al, ). This discrepancy may result from differences in mechanical stress, orthodontic force and the dynamic cyclic axial compression protocol.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, Pierroz et al () reported a reduction in bone volume in β1‐AR‐knockout mice, while other studies reported an improvement in bone fragility by blocking β1‐AR (Song et al, ; Toulis, Hemming, Stergianos, Nirantharakumar, & Bilezikian, ). Furthermore, β1‐AR signalling is reported to present an anabolic stimulus in response to mechanical stimulation (Pierroz et al, ).…”
Section: Introductionmentioning
confidence: 92%
“…ADRB1 plays a critical protective role in hypoxia/reoxygenation-induced neonatal rat cardiomyocyte injury in vitro [ 47 ]. Swift et al indicated that ADRB1 agonist treatment during dobutamine disuse mitigates negative changes in cancellous bone microarchitecture and inhibits increases in osteocyte apoptosis [ 48 ]. In addition, Zapater et al proposed that Beta-adrenergic receptor-1 antagonist accelerates liver norepinephrine modulation of the pro-inflammatory response in CCl(4)-treated mice [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, others found that treatment of rats with propranolol or a leptin analog during 28 days of hindlimb unloading reduced unloading-associated bone loss; propranolol treatment effectively preserved bone formation and prevented increased bone resorption, while leptin analog treatment was only able to prevent changes in osteoclastic bone resorption ( 101 ). Conversely, treatment of rats with a β1-adrenergic receptor agonist (dobutamine) attenuated hindlimb unloading-induced bone loss, prevented the decline in bone formation induced by unloading, and diminished unloading-induced osteocyte apoptosis ( 102 , 103 ).…”
Section: Nerves and Skeletal Adaptationmentioning
confidence: 99%